In the Presence of the Sublime Qur’an - Andrew C. Smith (International Institute of Islamic Thought, 2017)
This volume represents an especially modern viewpoint with regard to understanding the Qur’an and its message, while also being firmly embedded in traditional approaches and methods for its interpretation. The commentary consists of a number of lectures originally given in Persian by Abdolali Bazargan as a weekly lecture series in Irvine, CA. These lectures, a portion of which have been translated and edited into this single volume, were initially presented to groups of lay Muslims interested in the general theme of “becoming acquainted with the Qur’an” (p. xiv). The author, Abdolali Bazargan, is part of the laity himself: an architect by profession. While not having been fully trained in the traditional sciences 98 The American Journal of Islamic Social Sciences 34:2 of Qur’anic interpretation, his strong interest in Qur’anic exegesis (according to the editor) has led him to spend “the last 55 years researching it and writing 20 books in the field of Qur’anic sciences” (p. xiv). This volume is thus a lay commentary on the Qur’an’s “short surahs,” namely al-Fātiḥah and the last juz’ (chapters 78-114). Although no specific argument or thesis holds the entirety of the work together, it nevertheless stands as a representative sample of modern (educated) Muslim engagement with the text of the Qur’an and its ramifications for their lived religious tradition, particularly in the modern world ...